Bioactivity-guided isolation of potential antidiarrheal constituents from Euphorbia hirta L. and molecular docking evaluation - Wu, Junkai; Zhang, Xiaomeng; Guo, Liyang; Sheng, Zunlai (Frontiers in Veterinary Science, 2024)
Background: Euphorbia hirta L., a member of the Euphorbiaceae family, is extensively used as a folk medicine across various regions. In China, its decoction is traditionally consumed to alleviate diarrhea. This study aimed to evaluate the antidiarrheal activities of Euphorbia hirta and to identify its bioactive constituents through a bioactivity-guided isolation technique. Methods: Oral administration of E. hirta extract to mice was conducted to assess its effects on diarrhea. The anti-diarrheal effects were investigated in an aqueous extract and in three fractions of varying polarities derived from the aqueous extract, as well as in different eluates from D-101 macroporous resin, and in the compounds quercitrin and isoquercitrin, using mouse models with castor oil-induced diarrhea. Results: The aqueous extract demonstrated significant anti-diarrheal activities in a dose-dependent manner in the castor oil-induced diarrheal model. Notably, the ethyl acetate (EtOAc) fraction showed prominent effects. Through bioactivity-guided isolation, two major compounds, isoquercitrin and quercitrin from the active fraction were found to possess antidiarrheal effects. Molecular docking studies revealed that the affinity energy of isoquercitrin and quercitrin were -8.5 and -8.2 kcal mol-1, respectively, which were comparable to the reference drug loperamide, with an affinity energy of -9.1 kcal mol-1. Conclusion: This research provides evidence supporting the development of E. hirta as a therapeutic agent for diarrhea, with isoquercitrin and quercitrin emerging as two key constituents that are likely responsible for its antidiarrheal activity. These findings validate the traditional use of E. hirta and highlight its potential as a natural treatment for diarrhea.